2018
DOI: 10.2147/jpr.s177716
|View full text |Cite
|
Sign up to set email alerts
|

Do liposomal bupivacaine infiltration and interscalene nerve block provide similar pain relief after total shoulder arthroplasty: a systematic review and meta-analysis

Abstract: ObjectiveControversy still exists regarding the efficiency and safety of liposomal bupivacaine (LB) vs interscalene nerve block (INB) for pain management after total shoulder arthroplasty (TSA). The aim of the present meta-analysis was to perform a relatively credible and overall assessment to compare the efficiency and safety of LB-based infiltration vs INB for pain management after TSA.MethodsThe PubMed, Cochrane Library, Web of Science, and EMBASE were systematically searched. Only studies published up to M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…22 However, controversies exist regarding its analgesic e cacy. 1,23 Many studies have failed to detect the differences in analgesic effects between liposomal bupivacaine and traditional long-term local anesthetics, especially at the 24 h mark after surgery 24,25 . Thus, this study aimed to explore the analgesic effect of the developed liposomal bupivacaine in detail.…”
Section: Discussionmentioning
confidence: 99%
“…22 However, controversies exist regarding its analgesic e cacy. 1,23 Many studies have failed to detect the differences in analgesic effects between liposomal bupivacaine and traditional long-term local anesthetics, especially at the 24 h mark after surgery 24,25 . Thus, this study aimed to explore the analgesic effect of the developed liposomal bupivacaine in detail.…”
Section: Discussionmentioning
confidence: 99%
“…However, controversies exist regarding its analgesic efficacy 1 , 23 . Many studies have failed to detect the differences in analgesic effects between liposomal bupivacaine and traditional long-term local anesthetics, especially at the 24 h mark after surgery 24 , 25 . Thus, this study aimed to explore the analgesic effect of the developed liposomal bupivacaine in detail.…”
Section: Discussionmentioning
confidence: 99%
“…However, the author mistakenly used a retrospective study [15] as RCT in their study. In the study of Sun et al, [19] the authors included 4 RCTs [ 4 , 6 , 16 , 20 ] and 3 retrospective studies [ 13 – 15 ] to compare ISB alone with LIA alone and found that both techniques provide similar overall pain relief and have similar opioid consumption, while patients treated with LIA experienced significantly less occurrence rate of complications after TSA. However, they contained some methodological shortcomings, data extraction, limited sample size, and high heterogeneity.…”
Section: Discussionmentioning
confidence: 99%